IMPROD biparametric MRI in men with a clinical suspicion of prostate cancer (IMPROD Trial): Sensitivity for prostate cancer detection in correlation with whole‐mount prostatectomy sections and implications for focal therapy. Issue 5 (22nd March 2019) - Merisaari, Harri; Jambor, Ivan; Ettala, Otto; Boström, Peter J.; Montoya Perez, Ileana; Verho, Janne; Kiviniemi, Aida; Syvänen, Kari; Kähkönen, Esa; Eklund, Lauri; Pahikkala, Tapio; Vainio, Paula; et al.
Abstract : Background: Prostate MRI is increasingly being used in men with a clinical suspicion of prostate cancer (PCa). However, development and validation of methods for focal therapy planning are still lagging. Purpose: To evaluate the diagnostic accuracy on lesion, region‐of‐interest (ROI), and voxel level of IMPROD biparametric prostate MRI (bpMRI) for PCa detection in men with a clinical suspicion of PCa who subsequently underwent radical prostatectomy. Study Type: Prospective single‐institution clinical trial (NCT01864135). Population: Sixty‐four men who underwent radical prostatectomy after IMPROD bpMRI performed in prebiopsy settings. Field Strength/Sequence: IMPROD bpMRI consisted of T2 ‐weighted imaging (T2 w) and three separate diffusion‐weighted imaging acquisitions with an average acquisition time of 15 minutes. Assessment: The diagnostic accuracy of prospectively reported manual cancer delineations and regions increased with 3D dilation were evaluated on the voxel level (volume of 1.17 mm 3, 1 mm 3, 125 mm 3 ) as well as the 36 ROI level. Only PCa lesions with a diameter ≥ 5 mm or any Gleason Grade 4 were analyzed. All data and protocols are freely available at:http://petiv.utu.fi/improd Statistical Tests: Sensitivity, specificity, accuracy. Results: In total, 99 PCa lesions were identified. Forty (40%, 40/99) had a Gleason score (GS) of >3 + 4. Twenty‐eight PCa lesions (28%, 28/99) were missed by IMPROD bpMRI, three (7.5%, 3/40) with GS >3 + 4. 3D dilation of manual cancer delineations in all directions by ~10–12 mm (corresponding to the Hausdorff distance) was needed to achieve sensitivity approaching 100% on a voxel level. Data Conclusion: IMPROD bpMRI had a high sensitivity on lesion level for PCa with GS >3 + 4. Increasing 3D lesion delineations by ~10–12 mm (corresponding to the Hausdorff distance) was needed to achieve high sensitivity on the voxel level. Such information may help in planning ablation therapies. Level of Evidence: 1 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2019;50:1641–1650.